Information technology applications in construction safety assurance - Skibniewski, Mirosław J. (Journal of Civil Engineering and Management, 2014)
Through analysis of articles published from 2006 to July 2014 this paper summarizes the topics of research and the institutions where research was conducted in the field of computer-based construction safety engineering management. One hundred and thirty-six articles published during this time focused on Information Technology (IT) applications in this field were selected for analysis. The underlying research topics and their related IT implementations are discussed, and research trends in allied specialties are identified.